Naturally Occurring Genetic Alterations in Proximal TCR Signaling and Implications for Cancer Immunotherapy - Kent, Andrew; Longino, Natalie V.; Christians, Allison; Davila, Eduardo (Frontiers in Immunology, 2021)
T cell-based immunotherapies including genetically engineered T cells, adoptive transfer of tumor-infiltrating lymphocytes, and immune checkpoint blockade highlight the impressive anti-tumor effects of T cells. These successes have provided new hope to many cancer patients with otherwise poor prognoses. However, only a fraction of patients demonstrates durable responses to these forms of therapies and many develop significant immune-mediated toxicity. These heterogeneous clinical responses suggest that underlying nuances in T cell genetics, phenotypes, and activation states likely modulate the therapeutic impact of these approaches. To better characterize known genetic variations that may impact T cell function, we 1) review the function of early T cell receptor-specific signaling mediators, 2) offer a synopsis of known mutations and genetic alterations within the associated molecules, 3) discuss the link between these mutations and human disease and 4) review therapeutic strategies under development or in clinical testing that target each of these molecules for enhancing anti-tumor T cell activity. Finally, we discuss novel engineering approaches that could be designed based on our understanding of the function of these molecules in health and disease.